Macroalgas marinhas bentônicas em um trecho da APA da Baleia Franca, Litoral Sul de Santa Catarina, Brasil - Zago, Laura Reolon (My University, 2022)
Habitat destruction and overexploitation of natural resources are constant threats to marine ecosystems, and conservation efforts require consistent action.. The floristic inventory of a given area is essential to understand the transition of species with the environment and to draw up effective conservation and management plans. Marine macroalgae are fundamental in structuring coastal communities, forming the basis of the trophic chain and serving as a habitat for other organisms, in addition to having relevant economic importance. This study aimed to explore the floristic composition of marine macroalgae in an area of the Environmental Protection Area of Baleia Franca - APABF, which includes the beaches of Rosa Norte, Vermelha and Ouvidor, in order to support future studies and planning for conservation and contribute to the knowledge of the State's biodiversity. Samplings were carried out in the mesolittoral zone of the rocky shores, using the sweeping method, in the months of August, September and November 2022, during low tide. The species were identified with specific bibliographic aid, comparative means and by a professional in the area, totaling 61 species, 35 belonging to the phylum Rhodophyta, 15 to the phylum Chlorophyta and 11 to the phylum Ochrophyta (Phaeophyceae). Praia do Ouvidor had the highest number of species (45), followed by Praia do Rosa Norte (38) and Praia Vermelha (35). The results obtained were compared with studies carried out in nearby areas in order to understand more about the target community of study. Among the sampled species, Gastroclonium parvum (Hollenberg) C.f. Chang & B.M. Xia was identified as a new occurrence for the coast of Santa Catarina. The data from the present study may serve as a basis for future work, enabling the modification between environmental changes and floristic changes. [resumo fornecido pelo autor]
A destruição de habitats e exploração exagerada de recursos naturais são ameaças constantes aos ecossistemas marinhos, e esforços para conservação exigem ações consistentes. O inventário florístico de uma determinada área é fundamental para compreender as interações das espécies com o ambiente e traçar planos de conservação e manejo eficazes. As macroalgas marinhas são fundamentais na estruturação das comunidades costeiras, formando a base da cadeia trófica e servindo como habitat para outros organismos, além de apresentarem relevante importância econômica. Este estudo teve como objetivo explorar a composição florística das macroalgas marinhas de uma zona da Área de Proteção Ambiental da Baleia Franca, que compreende as Praias do Rosa Norte, Vermelha e do Ouvidor, a fim de subsidiar futuros estudos e planejamentos para conservação e contribuir para conhecimento da biodiversidade do Estado. As amostragens foram realizadas na zona do mesolitoral dos costões rochosos, por meio do método de varredura, nos meses de agosto, setembro e novembro de 2022, no período de maré baixa. As espécies foram identificadas com auxílio bibliográfico específico, meios comparativos e por profissional da área, totalizando em 61 espécies, sendo 35 pertencentes ao filo Rhodophyta, 15 ao filo Chlorophyta e 11 ao filo Ochrophyta (Phaeophyceae). A Praia do Ouvidor apresentou o maior número de espécies (45), seguida da Praia do Rosa Norte (38) e da Praia Vermelha (35). Os resultados obtidos foram comparados com estudos realizados em áreas próximas a fim de compreender mais sobre a comunidade alvo de estudo. Entre as espécies amostradas, identificou-se Gastroclonium parvum (Hollenberg) C.F.Chang & B.M.Xia como uma nova ocorrência para o litoral catarinense. Os dados do presente estudo poderão servir como base para trabalhos futuros, possibilitando a relação entre as alterações ambientais com as eventuais alterações florísticas. [resumo fornecido pelo autor]
Keywords: Biologia; Biodiversidade marinha; Algas marinhas; Gerenciamento costeiro - Santa Catarina; Proteção ambiental